Mortality of Critically Ill Children Requiring Continuous Renal Replacement Therapy: Effect of Fluid Overload, Underlying Disease, and Timing of Initiation*. Issue 4 (April 2019) - Cortina, Gerard; McRae, Rosemary; Hoq, Monsurul; Donath, Susan; Chiletti, Roberto; Arvandi, Marjan; Gothe, Raffaella M.; Joannidis, Michael; Butt, Warwick
Abstract : Objective: To identify risk factors associated with mortality in critically ill children requiring continuous renal replacement therapy. Design: Retrospective observational study based on a prospective registry. Setting: Tertiary and quaternary referral 30-bed PICU. Patients: Critically ill children undergoing continuous renal replacement therapy were included in the study. Interventions: Continuous renal replacement therapy. Measurements and Main Results: Overall mortality was 36% ( n = 58) among the 161 patients treated with continuous renal replacement therapy during the study period and was significantly higher in patients on extracorporeal membrane oxygenation (47.5%, 28 of 59) than in patients not requiring extracorporeal membrane oxygenation (28.4%, 29 of 102; p = 0.022). According to the admission diagnosis, we found the highest mortality in patients with onco-hematologic disease (77.8%) and the lowest in patients with renal disease (5.6%). Based on multivariate logistic regression analysis, the presence of higher severity of illness score at admission (adjusted odds ratio, 1.49; 95% CI, 1.18–1.89; p < 0.001), onco-hematologic disease (odds ratio, 17.10; 95% CI, 4.10–72.17; p < 0.001), fluid overload 10%–20% (odds ratio, 3.83; 95% CI, 1.33–11.07; p = 0.013), greater than 20% (odds ratio, 15.03; 95% CI, 4.03–56.05; p < 0.001), and timing of initiation of continuous renal replacement therapy (odds ratio, 1.01; 95% CI, 1.00–1.01; p = 0.040) were independently associated with mortality. In our population, the odds of dying increases by 1% for every hour of delay in continuous renal replacement therapy initiation from ICU admission. Conclusions: Mortality in children requiring continuous renal replacement therapy remains high and seems to be related to the underlying disease, the severity of illness, and the degree of fluid overload. In critically ill children at high risk for developing acute kidney injury and fluid overload, earlier initiation of continuous renal replacement therapy might result in decreased mortality. Abstract : Supplemental Digital Content is available in the text.